Kübizmin sinemaya etkisi: Otomatik Portakal filminin çözümlenmesi - Atasoy, Ayşe Duygu (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / İletişim Tasarımı Anabilim Dalı / İletişim Tasarımı Bilim Dalı, 2014)
Bu çalışmada kübizm sinemaya etkisi Stanley Kubrick'in filmi olan Otomatik Portakal üzerinden incelenmiştir. Çözümleme üç temel noktada yapılmıştır; mitoloji, kurgu ve ikilikler. Çözümleme için filmin içerisinden 101 plan seçilerek Roland Barhes'ın göstergebilimsel çözümlemesine göre yananlam ve düzanlam olarak incelenmiştir.

In this study, the influence of Cubism on Film is analysed taking Stanley Kubrick's film "Clockwork Orange" based on the novel by Anthony Burgess as a basis. The film is analysed in terms of three basic elements; mythology, editing and contradictions. In the course of the study 101 plans are selected, compared and interpreted regarding their direct and indirect meaning according to Roland Barthes' visual-semiotics study. As a result of the study some plans can be said to consist of cubic elements which are explained in details and "Clockwork Orange" may be described as a Cubist film. Key Words: Cinema, Stanley Kubrick, Cubism, Clockwork Orange, Roland Barthes
The influence of cubism on film / analysis of "Clockwork Orange"
Keywords: Sahne ve Görüntü Sanatları; Performing and Visual Arts